1984
DOI: 10.1210/jcem-59-1-79
|View full text |Cite
|
Sign up to set email alerts
|

Return of Gonadal Function in Men with Prolactin-Secreting Pituitary Tumors*

Abstract: Gonadal function was evaluated in 10 men [33 +/- 17 (SD) yr] with pituitary tumors and hyperprolactinemia (47-2550 ng/ml) using nocturnal penile tumescence (NPT), semen analysis, urinary LH and FSH excretion, and diurnal variation of serum testosterone and PRL. Results were compared to 16 normal subjects (33 +/- 13 yr). NPT was decreased in tumor patients as demonstrated by reduced maximum circumference change (P less than 0.01) and total tumescence time (P less than 0.05). Semen analysis was examined in 5 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, improvement of hypogonadism is often insufficient even after these treatment regimens. Although successful transsphenoidal extirpation of prolactin-secreting tumours has been reported (Pont et al, 1979), many of the procedures resulted in inadequate control of hyperprolactinaemia, leaving hypogonadism and impotence unchanged (Carter et al, 1978;Franks et al, 1978). Spontaneous recovery of testicular function after treatment does not occur in cases of prolactinoma with persistent postoperative hyperprolactinaemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, improvement of hypogonadism is often insufficient even after these treatment regimens. Although successful transsphenoidal extirpation of prolactin-secreting tumours has been reported (Pont et al, 1979), many of the procedures resulted in inadequate control of hyperprolactinaemia, leaving hypogonadism and impotence unchanged (Carter et al, 1978;Franks et al, 1978). Spontaneous recovery of testicular function after treatment does not occur in cases of prolactinoma with persistent postoperative hyperprolactinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…hyperprolactinaemia per se causes testicular dysfunction leading to hypogonadism Faglia et al, 1977). Recovery of testicular function occurs after transsphenoidal surgery of the macroadenomas, with or without oral administration of dopaminergic agonists or bromocriptine (Arafah et al, 1981;Murray et al, 1984). It has been reported that recovery of testicular function takes place only several months after serum prolactin levels are normalized (Arafah et al, 1981).…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, hypersecretion of prolactin resulting from a pituitary prolactinoma is a major cause of amenorrhea in women and impairs fertility in men [35], [36], but the specific mechanisms underlying these inhibitory effects on fertility remain unresolved. In sheep, administration of thyrotropin-releasing hormone (TRH), a potent stimulator of prolactin secretion, disrupted the estradiol-induced preovulatory surge of LH [37].…”
Section: Physiological Significance Of Gonadotrope/lactotrope Associamentioning
confidence: 99%
“…For example, several studies have suggested that libido is primarily affected, and that impo tence associated with hyperPRL occurs secondarily to de creased sexual desire [5,35]. In another recent study, noc turnal penile tumescence was reduced in hyperprolactin emic men both in terms of reduced maximum circumfer-ence change and decreased tumescence time, an indication of organic impotence [29], Thus, despite the fact that sexual dysfunction associated with hyperPRL in men is readily treatable [22], very little is known about the mechanisms b\ which hyperPRL affects libido and potency, and to what degree the accompanying hypogonadism may contribute to these effects [14,31].…”
mentioning
confidence: 98%